Common and Rare Variants Genetic Association Analysis of Circulating Neutrophil Extracellular Traps - Donkel, Samantha J.; Portilla Fernández, Eliana; Ahmad, Shahzad; Rivadeneira, Fernando; van Rooij, Frank J. A.; Ikram, M. Arfan; Leebeek, Frank W. G.; de Maat, Moniek P. M.; Ghanbari, Mohsen (Frontiers in Immunology, 2021)
Introduction: Neutrophils contribute to host defense through different mechanisms, including the formation of neutrophil extracellular traps (NETs). The genetic background and underlying mechanisms contributing to NET formation remain unclear. Materials and Methods: We performed a genome-wide association study (GWAS) and exome-sequencing analysis to identify common and rare genetic variants associated with plasma myeloperoxidase (MPO)-DNA complex levels, a biomarker for NETs, in the population-based Rotterdam Study cohort. GWAS was performed using haplotype reference consortium(HRC)-imputed genotypes of common variants in 3514 individuals from the first and 2076 individuals from the second cohort of the Rotterdam Study. We additionally performed exome-sequencing analysis in 960 individuals to investigate rare variants in candidate genes. Results: The GWAS yielded suggestive associations (p-value < 5.0×10-6) of SNPs annotated to four genes. In the exome-sequencing analysis, a variant in TMPRSS13 gene was significantly associated with MPO-DNA complex levels (p-value < 3.06×10-8). Moroever, gene-based analysis showed ten genes (OR10H1, RP11-461L13.5, RP11-24B19.4, RP11-461L13.3, KHDRBS1, ZNF200, RP11-395I6.1, RP11-696P8.2, RGPD1, AC007036.5) to be associated with MPO-DNA complex levels (p-value between 4.48×10-9 and 1.05x10-6). Pathway analysis of the identified genes showed their involvement in cellular development, molecular transport, RNA trafficking, cell-to-cell signaling and interaction, cellular growth and proliferation. Cancer was the top disease linked to the NET-associated genes. Conclusion: In this first GWAS and exome-sequencing analysis of NETs levels, we found several genes that were associated with NETs. The precise mechanism of how these genes may contribute to neutrophil function or the formation of NETs remains unclear and should be further investigated in experimental studies.